The therapeutic effect of performing arts from a psychoanalytical perspective - Marugán, Jorge (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2023)
This work analyses the therapeutic effects of performing arts and the different psychological processes that this artistic modality puts into play from the perspective of Sigmund Freud y Jacques Lacan. For this, it analyzes the concept of identification, first as a way of satisfying repressed desires, and secondly as a constitutive way of identity. The importance of sharing the emotional effect of a fiction to affirm the representation of a subject is then analyzed. Next, the function of two basic elements of performing arts is established: the setting and the curtain. It also shows that the importance of repetition and historization is revealed in approachment of trauma. The benefits of performing arts as a sublimation are exposed from the artist’s savoir faire. As an original contribution, two structures that organize two models of artistic creation are established: beautiful creation and shocking creation. Finally, taking as reference the Sophocles Antigone, the ethical and moral function of the represented act is justified.